Factors Affecting Dividend Policy in Financial Sector Companies in Indonesia: Panel Data Analysis - Nur Syamsiyah; Wulandari (LPPM Universitas Terbuka, 2022)
This study aims to analyze the factors that influence dividend policy in financial sector companies in Indonesia. The independent variables in this study are profitability, leverage, managerial ownership, and firm size. While the dependent variable used is dividend policy. Findings. The results showed that simultaneously all independent variables (leverage, firm size, profitability, and managerial ownership) affected dividend policy (the dependent variable). The percentage of influence of all variables used in this study on dividend policy is 72.52%. At the same time the rest is influenced by other variables equal to 27.48%. Partially, profitability and firm size have a positive relationship to dividend policy.